Education and critical thinking in the training of the person - Sosa Sanchez, Vladimir Junior (2023)
In this article, three key points will be addressed that will lead us to understand education and its relationship with critical thinking as part of the formation of the person. In the first place, the meaning of education in Paulo Freire will be analyzed, who was very committed to Latin American education, in this sense education is not a solitary activity, on the contrary, it is participatory that does not end within the classroom, since it transcends out of school. An education that allows the students to rediscover themself in their thinking so they can develop their autonomy from school. Secondly, the essential aspects of critical thinking will be addressed from a philosophical perspective, since critical thinking is part of the initial development of children and since it is not promoted in a timely manner, it disappears throughout the educational process. Thirdly, the formation of the person from philosophy will be analyzed. In this sense, philosophy will be an answer to understand the socio-educational structures of our countries, and we can clarify the importance of a philosophical education, where the students are not only the protagonist of their education, but teachers and students are co-educators, because the educational task is not absolute nor is knowledge closed.